Glycemic Index Values of Rice Varieties that are Commonly Available in Markets in Bangladesh - Kabir, Enamul; Hossain, Md Tofazzal; Hossain, Mohammad Anowar; Ray, Shuma Rani; Bhuiyan, Muhammad Javidul Haque (Jurnal Gizi dan Pangan, 2021)
Glycemic Index (GI) of six common rice varieties in the local markets of Bangladesh was assessed and categorized in this study to investigate manipulative varietal performance for the time being. After overnight fasting, each of ten selected healthy non-diabetic volunteers (males and females in ratio of 1:1) was fed with reference food (50 g glucose) and test foods (50 g carbohydrate-containing different rice varieties) in every two days intervals. After feeding, glucose levels (mmol/l) were measured at 0, 15, 30, 45, 60, 90 and 120 minutes. Incremental Area Under Curve (IAUC) of reference food and test food (avoiding the area beneath the baseline of reference food) was calculated to measure GI values. Amylose content (%) of different test foods was measured from the standard curve obtained from the spectrophotometric analysis after alcoholic-alkaline gelatinization that was followed by acidification and iodine mixing. The result showed that the GI values were 59.7±3.4; 50.5±2.6; 57.8±2.8; 51.3±2.3; 56.9±3.9 and 44.6±2.1, while the amylose content (%) were 23.6±0.6; 26.7±0.9; 21.3±0.7; 28.3±1.1; 22.2±2.3 and 29.8±1.5 for Nizershail, BRRI Dhan 29, Chinigura, Kalijira, Hybrid Hera Dhan 12 and Sworna, respectively. Moreover, the existing inverse relationship between the GI values and amylose content in this study was similar to other researchers’ findings. Categorization of the test foods based on the observed GI values ranked Sworna, BRRI Dhan 29 and Kalijira as low GI rice varieties that could be beneficial for consumption by diabetics as well as healthy individuals.